Eliyan, Mustafa. “The Poet and His Poetic Experience in Light of Surat Al-Shuʿarā’ (The Poets),” Year 3, Issue 12 (Spring 1418-1419 AH/ 1998 CE), Pp. 51-76. - عليان, مصطفى (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 1998)
Mustafa Eliyan’s study demonstrates that the poetic experience—if it is produced by an Islamic personality—is one of a religious and moral nature in its characteristics of faith, righteous deeds, remembrance of Allah, defense against oppression, and in its mental and psychological elements and their belief-based controls; whereas, righteousness and truth are the sources of the experience and its destination, its foundational launching point, and intellectual ending point. The Muslim poet is tasked with transmitting to people thoughts and concepts on human beings, life, and the universe, and to work on bringing these images closer to their minds by relating them to their tangible reality as experienced by people. This requires display and clarity, honesty in feeling, and sincerity in expressing it. And this cannot be ascertained without piety (taqwā) and certitude (yaqīn).